The Influence of Authentic Museumscape on Satisfaction and Visitor Happiness: A Study of Museums in Indonesia - Dini Mustika Buana Putri (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of Authentic Museumscape on visitor satisfaction and happiness and the mediating role of satisfaction. The study used a quantitative approach with the SEM-AMOS method on 120 respondents visiting the National Museum of Indonesia. In recent decades, museums in Indonesia have continued to transform to strengthen their image and increase the attractiveness of tourist visits. The results show that Authentic Museumscape has no significant effect on satisfaction (β = -0.011; p > 0.05), but has a significant positive effect on happiness (β = 0.704; p < 0.05). Satisfaction also has a significant positive effect on happiness (β = 0.47; p < 0.05), but does not mediate the relationship between Authentic Museumscape and happiness (p = 0.918). These findings indicate that visitor happiness is more influenced by direct experiences that are emotional and meaningful. This study contributes to the development of the Authentic Museumscape concept and provides practical implications for the management of experience-based museums. Specifically, this study makes three main contributions, namely: (1) developing a new construct of Authentic Museumscape as an integration between servicescape and authentic happiness; (2) testing an integrated structural model that links the physical environment, satisfaction, and happiness; and (3) enriching the cultural tourism literature in the context of developing countries, especially Indonesia.